Administrative management and labor performance in an educational entity in Arequipa in the situation of COVID-19 - Fernandez Sanchez, Diego Gonzalo (2021)
The objective of this investigation was to define the relationship between administrative management variables and work performance in teachers of the "Andenes de Chilina"  Educational Institution,Arequipa, 2020. Methodologically, it is a  pure research, also known as fundamental. The research level was  correlational, in which the relationship between the two variables  under study was determined. We worked under the hypothetical-deductive method with a quantitative and crosssectional approach,  because the measurement was carried out only once in time. The  sample population consisted of 28 teachers of both sexes, who are  in the basic educational levels (initial, primary and secondary). The results obtained, according to Pearson's correlation statistical test  applied to our variables under study: administrative management and work performance, showed an r = 0.834 (high positive correlation) with a significance level of 0.000, which was lower than  the expected value (p < 0.05). For this reason, the alternative  hypothesis was accepted, rejecting the null hypothesis. The conclusion was that there is a positive and significant relationship between administrative management and teacher job performance at the "Andenes de Chilina" Educational Institution,Arequipa, 2020.